A Critique of Inclusive Growth: Problems of Modernization of Agriculture. (1st October 2014) - Saumya Chakrabarti
Abstract : Diversification of agriculture and allied production processes intended for the high-value domestic and export markets create the scope for intervention of big capital in agriculture through variety of contracts. However, this intrusion of capital in the fields of agricultural production and distribution displaces the petty production-based rural non-farm economy (RNFE), having a symbiotic relation with the traditional subsistence agriculture. The change in the cropping pattern in favour of high-value-crop and diversion of resources toward the modern animal husbandry initiate an inclusion of the relatively advanced and asset-rich parts of agriculture and allied activities into the growing global economy, but it breaks the close links between the subsistence agriculture and petty RNFE. Furthermore, the population engaged in urban food retailing is also displaced by the intrusion of the supermarket chains. Last but not the least, if crop-diversification is undertaken through large-scale substitution of basic cereal production, it seriously affects the micro- and macro-food-security leading to immiserization of the rural and urban poor.